Report of three patients with extensive neurocysticercosis in rural southern Tanzania: neurological, serological and neuroradiological findings - Stelzle, D.; Makasi, C.; Welte, T. M.; Ruether, C.; Schmidt, V.; Gabriel, S.; Bottieau, E.; Fleury, A.; Ngowi, B. J.; Winkler, A. S.; Trevisan, Chiara; Van Damme, Inge; et al. (Journal of Medical Case Reports, 2023)
Background: Neurocysticercosis (NCC) is common in eastern Africa, but disease presentation varies considerably. Most patients have single or few NCC-typical lesions in their brain but some present with a large number of lesions. We present three patients with positive antibody-based serology for Taenia solium cysticercosis screened at the Vwawa district hospital, Mbozi district, southern Tanzania, in whom extensive NCC was confirmed by neuroimaging. Case presentations: Patient 1 was a 55-year-old female from the tribe Malila smallholder farmer who has had four generalized tonic–clonic epileptic seizures over a period of 11 years and one episode of transient left hemiparesis one year before seizure onset. The patient also reported monthly to weekly episodes of severe, progressive, unilateral headache. The computed tomography (CT) scan of the brain showed 25 NCC lesions of which 15 were in the vesicular stage. Patient 2 was a 30-year-old male from tribe Nyha mechanic who reported monthly episodes of moderate to severe, progressive, bilateral headache, but no epileptic seizures. The CT scan showed 63 NCC lesions of which 50 were in the vesicular stage. Patient 3 was a 54-year-old female from the tribe Malila smallholder farmer who suffered from frequent generalized tonic–clonic epileptic seizures with potential signs of focal seizure onset. She also reported weekly to daily episodes of severe, progressive, unilateral headache. The CT scan showed 29 NCC lesions of which 28 were in the vesicular stage. Conclusions: Clinical presentation of NCC with multiple brain lesions varies considerably ranging from few epileptic seizures and severe headache to severe epilepsy with frequent epileptic seizures. Individuals with neurological signs/symptoms that may be due to NCC, based for example on epidemiological criteria or serological evidence of cysticercosis, are recommended to undergo neuroimaging before anthelminthic treatment is considered.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Case report; Epilepsy; Neglected tropical disease; Neurocysticercosis; Taenia solium